ANALISIS SEKTOR EKONOMI UNGGULAN DALAM MENDORONG PERTUMBUHAN EKONOMI KABUPATEN MAGELANG TAHUN 2015-2019 - Yusuf, Maulana; Panjawa, Jihad Lukis (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2022)
The development process of an area cannot run smoothly and optimally if the process does not match its potential. Magelang Regency actually has potential sectors to be developed and is able to make a good contribution to GRDP. This study aims to analyze and identify leading, competitive sectors which are then used as a driver for economic growth and regional development of Magelang Regency. The data used in this research is secondary data. While the research method uses Location Quotient (LQ) analysis and Shift-Share analysis.Based on the results of the analysis, it shows that there are several prominent economic sectors in the Magelang Regency, namely 1) the agriculture, forestry and fisheries, 2) the mining and quarrying 3) the clean water supply, waste processing and recycling, 4) the transportation and warehousing sector, 5) accommodation and food and drink provision, 6) information and communication, 7) real estate, 8) government administration, 9) education services and 10) other services. Apart from that it is a non-base sector. Meanwhile, in the calculation of the shift share analysis, there are several sectors that have experienced a shift. One of them is the agriculture, forestry and fisheries sectors. However, as a whole, all sectors in Magelang regency are related to one another and have a positive influence on the overall regional output growth.